On General Sum-Connectivity Index and Number of Segments of Fixed-Order Chemical Trees - Muzamil Hanif; Akhlaq A. Bhatti; Hicham Saber; Adel A. Attiya; Akbar Ali (Journal of Mathematics)
Nowadays, one of the most active areas in mathematical chemistry is the study of the mathematical characteristics associated with molecular descriptors. The primary objective of the current study is to find the largest value of χα of graphs in the class of all fixed-order chemical trees with a particular number of segments for α>1, where χα is the general sum-connectivity index, which is a molecular descriptor introduced about one and a half decades ago. Similar results for general trees are also found.